Urin Kambing sebagai Pupuk Organik Cair Pembibitan Lada Perdu (Piper ningrum L.): Selmitri, Setiawan - Selmitri, Setiawan Selmitri, Setiawan (Sumber Penyuluhan Pertanian Indonesia, 2023)
Goat urine is a liquid organic fertilizer that can increase the growth of shrub pepper nurseries grown on ultisol soil, with the ability of goat urine to improve the quality of ultisol soil physically, chemically, and biologically. The study aimed to obtain the best dose of goat urine POC to increase the growth of shrub pepper seedlings on ultisol soils. The research was conducted using a greenhouse and carried out in Pontianak City, West Kalimantan, Indonesia, from June to December 2021. The experiment was prepared using a complete randomized design, namely the influence of various doses of liquid organic fertilizer for goat urine with five levels (100 ml, 200 ml, 300 ml, 400 ml, and 500 ml). The results of the study obtained that the increasing dose of goat urine liquid organic fertilizer used for breeding shrub pepper can significantly affect the height of the seedlings, the diameter of the stem, the number of leaves, and the dry weight of the upper part of the plant. The best goat urine POC dose was obtained at the 400 ml treatment according to the variables of seedling height, stem diameter, and dry weight of the upper part of the plant, as well as on the variable number of leaves the best dose, namely at the 200 ml treatment.